Eco-printing Training with Blanket Technique to Improve the Skillset of the Members of Family Empowerment and Welfare (PKK) - Sri Rustiyaningsih; Veronika Agustini Srimulyani; Haris Wibisono (Faculty of Economics Universitas Sarjanawiyata Tamansiswa, 2025)
Purpose Community service activities aim to provide additional skills and motivate members of the Family Empowerment and Welfare (PKK) to become entrepreneurs by providing skills training to make eco-fashion products that are in demand by the community and are environmentally friendly. In addition, the materials used are easily available from nature in the neighborhood. Methods - Interactive training methods are employed in workshops, which cover a range of topics including the cleaning of fabrics to remove impurities, the mordant of fabrics, blanket dyeing, the treatment of leaves and flowers, eco-printing, and fabric fixation. Result and discussions - The training was attended by 20 PKK members. The training started with the explanation of the materials, tools, leaf and flowers used in the production of eco-print products. The training participants were able to make eco-print products with pashmina media and 3 PKK members were able to make eco-print products with pashmina media as there were several PKK members who were absent. PKK members know natural materials that have tannins and can be used as eco-print media. In addition, PKK members are able to distinguish fixing materials that cause light and dark colors in eco-print products. Conclusion - Training participants have the opportunity to create eco-print products using woven pashmina material. Through this training, participants have expanded their understanding of leaves and flowers that contain high concentrations of tannins. While trainees are capable of producing products independently, they are not yet permitted to sell the products they create. Keywords: eco-print, pashmina, blanket, take leaf